Cartographies of New York and Other Postwar American Cities Art, Literature and Urban Spaces - Manolescu, Monica (Geocriticism and Spatial Literary Studies, 2018)
Cartographies of New York and Other Postwar American Cities: Art, Literature and Urban Spaces explores phenomena of urban mapping in the discourses and strategies of a variety of postwar artists and practitioners of space: Allan Kaprow, Claes Oldenburg, Vito Acconci, Gordon Matta-Clark, Robert Smithson, Rebecca Solnit, Matthew Buckingham, contemporary Situationist projects. The distinctive approach of the book highlights the interplay between texts and site-oriented practices, which have often been treated separately in critical discussions. Monica Manolescu considers spatial investigations that engage with the historical and social conditions of the urban environment and reflect on its mediated nature. Cartographic procedures that involve walking and surveying are interpreted as unsettling and subversive possibilities of representing and navigating the postwar American city. The book posits mapping as a critical nexus that opens up new ways of studying some of the most important postwar artistic engagements with New York and other American cities.